2022
DOI: 10.1021/acsomega.2c04419
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Protamine and Zn–Insulin Assembly: Exploring Biophysical Consequences

Abstract: The insulin−protamine interaction is at the core of the mode of action in many insulin formulations (Zn + insulin + protamine) and to treat diabetes, in which protamine is added to the stable form of hexameric insulin (Zn−insulin). However, due to the unavailability of quantitative data and a high-resolution structure, the binding mechanism of the insulin− protamine complex remains unknown. In this study, it was observed that Zn−insulin experiences destabilization as observed by the loss of secondary structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
5
2
Order By: Relevance
“…An earlier experimental and docking study by Aggarwal et. al . suggested increased flexibility of the complex upon binding, which is contrary to our results.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…An earlier experimental and docking study by Aggarwal et. al . suggested increased flexibility of the complex upon binding, which is contrary to our results.…”
Section: Discussioncontrasting
confidence: 99%
“… is a significant contributor to the binding energy. The fact that values are substantially lower than values indicates that hydrophobic interactions are not as significant as electrostatic interactions, which is consistent with the experimental study done on an equimolar mixture of insulin and protamine . Therein, it was shown that the binding interactions between insulin and protamine are hydrophilic in nature.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations